PENGARUH FIRM SIZE, CURRENT RATIO, DEBT TO EQUITY RATIO, TOTAL ASSETS TURNOVER TERHADAP KINERJA KEUANGAN - Leonardo Krisman; Anissa Amalia Mulya (Jurnal Ilmiah Manajemen dan Akuntansi, 2025)
This research aims to examine the influence of Firm Size, Current Ratio, Debt to Equity Ratio, Total Assets Turnover on Finansial Performance. Firm Size, Current Ratio, Debt to Equity Ratio, Total Assets Turnover as an independent variable, Finansial Performance as the dependent variable. This research uses secondary data with a population of 44 companies, namely on Nikel sub sector mining companies listed on the Indonesian Stock Exchange in 2021-2024, 13 (thirteen) companies are the research sample with the observation year 2021-2024. The sampling technique used was purposive sampling with multiple linear regression analysis method. The results of this research show that partially and simultaneously Firm Size Influences Stock Price. Meanwhile, Current Rasio, Debt to Equity Ratio, Total Assets Turnover have No. Effects on Financial Performance.